Gestión de talento humano para el desarrollo académico de los alumnos de la Unidad Educativa “San José” de Guaytacama. - Peñaherrera Lopez, Pamela Del Rocio (2019)
This research project is based on the management of human talent and its impact on the academic development of students. Its objective is: To develop a teacher training program to promote the academic development of the students of the Educational Unit "San José" of Guaytacama. For the development of the research, the diagnosis of the factors of human talent management in the academic development of the students was made, through a survey applied to teachers, the research methodology is based on a positivist paradigm, therefore , the deductive method based on existing theories is applied, since a cause variable and an effect variable are determined, segmented into testing the theory in reality and describing it statistically to demonstrate the relationship between the variables and operationalize them. Based on these results, the need to design a training program for teachers and directors of the "San José" Educational Unit is established with a thematic line focused on promoting the academic development of students, which is implemented obtaining satisfactory results.